Site-specific localized labeling for efficient bio-sensing of drug resistant bacterial strains - Kock, Si Min (2016)
β-lactam antibiotics are a crucial class of drugs widely used to target bacterial infections. However, the frequent use and misuse of β-lactam antibiotics has resulted in the emergence of antibiotic resistance – a severe threat to global health – which is present dominantly through the production of β-lactamase. In response, our group sought to develop optical imaging probes that would enable the rapid and selective intracellular identification and imaging of β-lactamase activity in real-time. We hope the optical imaging probes would serve as a tool for diagnostic microbiology – to screen and identify resistant bacterial strains – to administer controlled antibiotic therapy and to enable more in-depth research in antibiotic resistance mechanisms.